Purulent Pericarditis with Greenish Pericardial Effusion Caused by Shewanella algae - Tan, Che-Kim (American Society for Microbiology (ASM), 2008)
We report the first case of purulent pericarditis with greenish pericardial effusion caused by Shewanella algae in a patient with gastric and gallbladder cancer. This case expands the reported spectrum of infection caused by S. algae and raises the possibility that S. algae is a causative pathogen for purulent pericarditis.